ENHANCING RECOVERY IN COMPLEX CLASTIC RESERVOIRS THROUGH DYNAMIC MODEL UPDATES AND PROACTIVE WELL MANAGEMENT - Murodov Sadriddin Nizomiddinovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article presents a practical, data-driven approach to improving oil recovery from mature, heterogeneous clastic reservoirs. The focus is on the operational use of surveillance  data  (production  logs,  tracers,  pressure  measurements)  and  updated sedimentological concepts to continuously refine the reservoir understanding. It details how revised parameters, such as sand body connectivity and permeability contrasts, directly influence the mapping of remaining oil saturation (ROS). Based on updated dynamic models, practical recommendations are formulated for conformance control in  waterflood  projects  and  the  targeted  placement  of  infill  wells.  The  paper demonstrates that a systematic model-update practice can significantly improve project economics  through  increased  well  success  rates  and  reduced  water  handling  costs, without the need for massive capital investment.